Evaluating Genre-Based Instruction through Error Analysis: Insights from Vocational Students’ Procedure Texts - Simanjuntak, Anni Alvionita; Rika Wahyuni Tambunan (JAMI: Jurnal Ahli Muda Indonesia, 2025)
Writing procedure texts in English is an important skill for vocational students, especially those in practice-based programs. These texts are used in workplaces to give instructions or explain steps clearly and accurately. The Genre-Based Approach (GBA) is often used to help students write better by teaching them the structure and purpose of different types of texts. While many studies have shown that GBA helps students organize their writing, few have looked closely at the language mistakes students still make after learning with this method. Methods. This study used a qualitative descriptive design to analyze the errors in 30 procedure texts written by students in the Audio-Visual Editing program at AKN Putra Sang Fajar Blitar. These texts were collected after students completed two cycles of learning with the GBA. The errors were analyzed using the Surface Strategy Taxonomy, focusing on four categories: omission, addition, misformation, and misordering. Two raters checked and coded the data, and additional data from teacher notes and student feedback were used to support the findings. Results. The results showed that most students could follow the correct structure of a procedure text. However, many still made language mistakes. Misformation (wrong word forms) and omission (missing words) were the most common errors. These errors often affected the clarity and meaning of the instructions. This shows that while GBA helps students with text organization, it does not always help improve grammar or sentence accuracy. Conclusions. Genre-based instruction helps students understand how to organize their writing, but it should be combined with a greater focus on grammar and language use. Teachers should include grammar practice and give detailed feedback on errors. This combination can help vocational students write more precise and more correct texts for real-world communication.